Epigenetics of obesity - O. M. Drapkina; O. T. Kim (Кардиоваскулярная терапия и профилактика, 2020)
The pathophysiology of obesity is complex and includes changes in eating behavior, genetic, epigenetic, environmental factors, and much more. To date, ~40 genetic polymorphisms are associated with obesity and fat distribution. However, since these options do not fully explain the inheritance of obesity, other options, such as epigenetic changes, need to be considered. Epigenetic modifications affect gene expression without changing the deoxyribonucleic acid sequence. In addition, environmental exposure during critical periods of development can affect the epigenetic tags and lead to obesity. A deeper understanding of the epigenetic mechanisms underlying obesity can aid in prevention based on lifestyle changes. This review focuses on the role of epigenetic modifications in the development of obesity and related conditions.